2023
DOI: 10.1039/d3dt00957b
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of 2D@3D hollow Prussian blue analogue as a high-performance bifunctional electrochemical sensor

Abstract: Prussian blue analogues (PBAs) is a family of classic coordination polymer. They have been widely applied into various fields including electrochemical sensors. Cubic nanoparticle is their common morphology. It is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the Ni 2p spectrum (Figure S10c), two main peaks at 856.3 and 874.1 eV can be assigned to Ni 2p 3/2 and Ni 2p 1/2 with their satellite peaks at 862.3 and 880.1 eV, respectively, which are ascribed to Ni 2+ . For the Co 2p spectra (Figure S10d), the peaks at around 781.8 and 796.9 eV can be assigned to Co 2p 3/2 and Co 2p 1/2 , respectively, which are attributed to Co 2+ . It can be observed that the peak positions and areas of Ni and Co ions were essentially similar before and after the redox reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ni 2p spectrum (Figure S10c), two main peaks at 856.3 and 874.1 eV can be assigned to Ni 2p 3/2 and Ni 2p 1/2 with their satellite peaks at 862.3 and 880.1 eV, respectively, which are ascribed to Ni 2+ . For the Co 2p spectra (Figure S10d), the peaks at around 781.8 and 796.9 eV can be assigned to Co 2p 3/2 and Co 2p 1/2 , respectively, which are attributed to Co 2+ . It can be observed that the peak positions and areas of Ni and Co ions were essentially similar before and after the redox reaction.…”
Section: Resultsmentioning
confidence: 99%
“…39 For the Co 2p spectra (Figure S10d), the peaks at around 781.8 and 796.9 eV can be assigned to Co 2p 3/2 and Co 2p 1/2 , respectively, which are attributed to Co 2+ . 66 It can be observed that the peak positions and areas of Ni and Co ions were essentially similar before and after the redox reaction. The results of the XPS spectra for PBA/MIL-53(NiFe)/NF show that its redox center is relatively stable, further confirming its structural stability.…”
Section: Electrocatalytic Behaviormentioning
confidence: 85%
“…A bifunctional electrochemical sensor based on the PBA was fabricated by Liu et al, for the detection of glucose and nitrite. They have demonstrated a facile and efficient method to fabricate a 2D@3D PBA material with excellent performance . Even though a few of these electrocatalysts have been reported for different applications, their poor conductivity limits their applicability and performance.…”
Section: Introductionmentioning
confidence: 99%
“…They have demonstrated a facile and efficient method to fabricate a 2D@3D PBA material with excellent performance. 15 Even though a few of these electrocatalysts have been reported for different applications, their poor conductivity limits their applicability and performance. The agglomeration of PBA particles due to fast crystallization is another concern affecting their performance.…”
Section: Introductionmentioning
confidence: 99%
“…With the current research exploration and utilization of the unique properties of PB-derived nanomaterials, the fields of explosives and fireworks are expected to experience significant progress and innovation . Ultimately, this will enhance key applications in national security and other fields. …”
Section: Introductionmentioning
confidence: 99%